Effects of Insurance on Child Labour: Ex-Ante and Ex-Post Behavioural Changes - Froelich, Markus; Landmann, Andreas (Journal of Development Studies, 2018)
In this paper we analyse possible effects of insurance on child labour. First, we develop a theoretical model that separates effects of insurance with and without a shock taking place. We then empirically test the hypotheses derived from the model by analysing the extension of a health insurance product in urban Hyderabad in Pakistan. Consistent with the theoretical model we develop in this paper, the reduction in child labour caused by the extension is largely due to an ex-ante feeling of protection as opposed to an ex-post shock-mitigation effect.
Created from Fastlane, Scopus look-up